The value of genetic and genomic technologies workshop summary - Institute of Medicine (U.S.); Wizemann, Theresa M.; Berger, Adam C.; Institute of Medicine (U.S.). Roundtable on Translating Genomic-Based Research for Health; Institute of Medicine (U.S.). Board on Health Sciences Policy; ebrary, Inc. (Washington, D.C. : National Academies Press, 2010)
"Knowing one's genetic disposition to a variety of diseases, including common chronic diseases, can benefit both the individual and society at large. The IOM's Roundtable on Translating Genomic-Based Research for Health held a workshop on March 22, 2010, to bring together diverse perspectives on the value of genetic testing, and to discuss its use in clinical practice"--home page.
Tumor-based screening for Lynch Syndrome -- Pharmacogenomic testing to guide warfarin dosing -- Genomic profiling -- Closing remarks.
"Roundtable on Translating Genomic-Based Research for Health, Board on Health Sciences Policy."
Includes bibliographical references.
Electronic reproduction.
Keywords: Genomics -- Congresses; Genomics -- Research -- Congresses; Human chromosome abnormalities -- Diagnosis -- Congresses; Genetic counseling -- Congresses; Genetic disorders -- Diagnosis -- Congresses; Electronic books